An exhibition of one's own: the Salón Femenino de Bellas Artes (Buenos Aires, 1930s-1940s) - Gluzman, Georgina Gabriela (2019)
From the late 1920s on, Buenos Aires witnessed the emergence of exhibitions of a separatist character for women artists. Their vast development, the extensive coverage by the press, and their links to feminist institutions have been ignored in traditional art historical literature. Focusing on the Salón Femenino organized by the Club Argentino de Mujeres, this article aims to reconstruct the organization of these events, to examine their reception, and to analyze the careers of some of the participating women artists. These exhibitions offer a new perspective for the analysis of a period of intense feminine artistic activity in Argentina.